Peningkatan Hasil Belajar PAI Materi Berwudhu Melalui Metode Demonstrasi Pada Peserta Didik Kelas II di SDN Hargowilis - I'ing Hildah (Islamic University of Indonesia, 2021)
This study aims to determine the increase in learning outcomes of ablutionmaterial after using the demonstration method. This research is a classroomaction research conducted on second grade students at SD NegeriHargowilis. The subjects of this study were second grade students at SDNegeri Hargowilis, Kokap, Kulon Progo semester 1 of the 2018/2019academic year. This research was conducted in two cycles, with each cycleconsisting of action planning, action implementation, observation, andreflection. The results showed that the implementation of learning ablutionmaterial using the demonstration method could improve student learningoutcomes in class II SD Negeri Hargowilis, Kokap, Kulon Progo. Theincrease in learning outcomes is indicated by an increase in learningactivities by 15.2% and the number of students who achieve learningcompleteness as much as 90%.Keywords: Demonstration Method; Improvement; Learning Outcomes,Wudhu.